Organic Anion Exudation by Lowland Rice (Oryza sativa L.) at Zinc and Phosphorus Deficiency - Hoffland, E; Wei, C; Wissuwa, M (Plant and soil, 2006)
The objectives of this paper were to determine (1) if lowland rice (Oryza sativa L.) plants respond similarly to low zinc (Zn) and phosphorus (P) availability by increased root exudation of low-molecular weight organic anions (LMWOAs) and (2) if genotypic variation in tolerance to low soil supply of either Zn or P is related to LMWOA exudation rates. Exudation of LMWOAs can increase bioavailability of both Zn and P to the plant, through partly similar chemical mechanisms. We used seven lowland rice genotypes and showed in two experiments that genotypes that grow relatively well on a soil with low Zn availability also grow well on a sparingly soluble Ca-phosphate (r = 0.80, P = 0.03). We measured exudation rates of LMWOAs on nutrient solution and found that both Zn and P deficiency induced significant increases. Among the LMWOAs detected oxalate was quantitatively the most important, but citrate is considered more effective in mobilizing Zn. Citrate exudation rates correlated with tolerance to low soil levels of Zn (P = 0.05) and P (P = 0.07). In a low-Zn-field we found an increased biomass production at higher plant density, which is supportive for a concentration-dependent rhizosphere effect on Zn bioavailability such as LMWOA exudation. We, for the first time, showed that tolerance to low Zn availability is related to the capacity of a plant to exude LMWOAs and confirmed that exudation of LMWOAs must be regarded a multiple stress response.